DESAIN FORECASTING PENJUALAN PADA ERAFONE ANDROID NATION PARAGON SEMARANG DENGAN METODE MOVING AVERAGE DAN EXPONENTIAL SMOOTHING - Agustiana, Tiara; Suhari, Yohanes (Information Technology and Telematics, 2018)
Abstract Erafone Android Nation Paragon Semarang engaged in the sale of mobile phones, the problem currently there is no sales forecasting system to predict sales every month, therefore company requires sales forecasting design, for the method used is moving average method and exponential smoothing with data objects existing sales at the company. The system development method uses the waterfall method. The results of the research are made, the creation of a forecasting design that can be used to forecast mobile phone sales for the following months and make this application useful for the company.